Efektifitas Penggunaan Kapur Terhadap R-Value Lempung Semen - Perpustakaan UGM, i-lib ([Yogyakarta] : Jurusan Teknik Mesin Fak. Teknik UGM, 2003)
One of parameters on bearing capacity of subgrade for pavement design is R-Value. Bearing capacity of soil could be improved by soil stabilization method. Lime modification could be used prior to soil stabilization. Aim of the research is to investigate the effectiveness of lime modification on R-Value of clay-portland cement stabilization. The R-Value tests were conducted on clay-portland cement mixtures using 6%, 8% and 10% of portland cement. The cla-portland cement mixtures were lime-modified using 1%, 2% and 3% of lime and cured for 3 days and 7 days. The research results show that the optimum effectiveness of lime modification on R-Value of clay-portland cement mixtures is the use of I% lime to dry weight of the mixtures with curing time of 7 days.